Perbandingan Kinerja Instrumen Investasi Berbasis Syariah dengan Konvensional di Pasar Modal Indonesia - Ida Syafrida; Indianik Aminah; Bambang Waluyo (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Performance Comparation between sharia instrument performance and conventional syariah The main objective of investors in investment activities is to get the profit. Similarly, investors in Islamic investment activities want the same things. But often the performance of sharia instruments deemed lower than conventional instruments, so market share Sharia-compliant investment instruments is still minimal. This research doing comparation performance index and mutual fund index between shariah based and conventional based. Based on the results of research that takes samples Islamic instruments of capital markets such as sharia Islamic stocks and sharia mutual funds, it is concluded that the performance of sharia-based investment instruments are not significantly different from the conventional investment instruments, even during the period of research Islamic investment instruments showed slightly better performance.  DOI:10.15408/aiq.v6i2.1230